ON THE BARLEY PLANTING METHODS ON DRAINED SOIL - Yu. I. Mitrofanov; A. E. Artemiev; N. A. Smirnova (Зерновое хозяйство России)
The article presents the study results of the barley planting methods on drained soil. The research was carried out in the experimental fields of the FSBSI ‘All-Russian Research Institute of Reclaimed Lands’. In the trials, conventional drill method of planting (SZ-3.6), band method of planting and broadcast method of planting were compared. It is established that barley on drained soil should be grown on the scallops of 40–80 mm height with local soil compaction under a ridge and indentation of the seeds into the soil. The yield increase with the ridge method of planting are 0.23–0.55 t/ha or 6.2–16.3% in relation to the conventional method of planting (SZ-3.6), the direct costs of producing 1 t of grain are reduced by 5.3–13.8%. The indentation of seeds into the soil with the ridge method of planting increased barley yield on 0.43 t/ha under its cultivation. A broadcast method of barley planting is of certain interest for the conditions of the northwest of the Non-Blackearth (chernozem) region. The labor productivity is increased by 1.5–3 times, labor costs per 1 hectare connected with planting operations are reduced by 37.6–58.4%, and fuel consumption is reduced by 7.4–39.2 %. With the use of seed spreaders, there is no need in separate auxiliary operations, special loaders and transport for seed transportation, the time of field work is shortened, the adaptability of seeding technology to soil-meliorative conditions is increased, the compacting effect of running systems of tractors and machines on soil is reduced (by 2–4 times).